Extraction and purification of theobromine using ionic liquids - Esteves, Pedro Duarte de Oliveira (2018)
Theobromine is an alkaloid present in cocoa and it is used in the treatment of atherosclerosis, hypertension, angina, among others. Due to its importance, the aim of this work consists on the development of an efficient and sustainable technology for the extraction of theobromine from cocoa beans. For the development of a purification technique for theobromine extracted from cocoa, aqueous biphasic systems (ABS) composed of ionic liquids (ILs) were initially studied to infer on the most promising systems. Cholinium-based ILs, based on a non-toxic and biocompatible cation, were used combined with two polymers (PPG 400 and PEG 400) and an inorganic salt (K3PO4). The respective phase diagrams at 298 K and atmospheric pressure were determined, as well as their extraction efficiencies for theobromine. The results obtained indicate that K3PO4 has a greater ability to induce the formation of ABS compared to PEG 400 and PPG 400. ABS consisting of K3PO4 also have a high potential for the extraction of theobromine, with extraction efficiencies ranging between 96.4 and 99.9 %. Based on the most promising ILs for the purification step, they were further used in aqueous solution to extract theobromine from cocoa beans, with extraction yields ranging between 4.5% and 6.5 wt%. Finally, ABS were applied to the aqueous solutions containing theobromine from the cocoa extract, with extraction efficiencies ranging between 96.7 and 99.0%.